(untitled) (Tạp chí Y học Cộng đồng, 2026)
Urinary tract infections (UTIs) are among the top five most common hospital-acquired infections. Annually, millions of patients are affected by healthcare-associated UTIs, posing a major challenge to medical facilities worldwide. Objective: To determine the antimicrobial resistance patterns and susceptibility profiles of each uropathogen isolated from inpatients with suspected UTIs who underwent urine culture at Tra Vinh General Hospital. Materials and Methods: A descriptive, retrospective cross-sectional study was conducted on 132 patients (or episodes). Bacterial strains were identified and antimicrobial susceptibility testing (AST) was performed using the Vitek 2 automated system. Data were recorded from medical records. Results: E. coli exhibited high resistance rates of >80% to Ampicillin, Piperacillin, and Fluoroquinolones (Ciprofloxacin). Bacterial isolates were more frequent than fungi (23.48% vs 8.33%). K. pneumoniae demonstrated 100% resistance to Ampicillin, Ampicillin-sulbactam, Cefepime, and Cefoxitin; resistance to Carbapenems, Aminoglycosides, and Fluoroquinolones ranged from 80% to 100%; and resistance to Cephalosporins exceeded 66.67%. P. aeruginosa showed a 50% resistance rate to Piperacillin-tazobactam, Piperacillin, Ceftazidime, Imipenem, Meropenem, and Ciprofloxacin. P. mirabilis was 100% resistant to Ampicillin, Piperacillin, Ciprofloxacin, and Tigecycline. Conclusion: It is essential to prioritize urine culture and antimicrobial susceptibility testing before antibiotic administration to guide appropriate treatment regimens, prevent misuse, and mitigate the risk of escalating antimicrobial resistance.